Determinants of Tax Ratio and Reform Efforts in Southeast Asia: Evidence from a Toda-Yamamoto Causality Approach - Yossinomita, Yossinomita; Hartanti, Rina; Saputri, Rista Zahra (Ekonomika, 2026)
This study analyzes tax reform and its determining factors affecting the tax ratio in Indonesia, Malaysia, India, and Singapore by using the Toda-Yamamoto causality approach. The findings reveal five significant causal relationships in Indonesia, including the impact of inflation (I) on the tax ratio (τ) at the 1% significance level (p = 0.0000), emphasizing the critical role of macroeconomic stability in optimizing tax revenue. In Malaysia, three significant causal relationships were identified, one of which is the effect of e-filing adoption (E) on the Corruption Perception Index (CPI) at a 10% significance level (p = 0.0670), suggesting that the digitalization of tax administration can enhance perceptions of governance and corruption. India exhibits five significant relationships, including the influence of the tax ratio (τ) on CPI at a 5% significance level (p = 0.0290), reinforcing the link between tax policy and public trust in government institutions. In Singapore, two significant relationships were found, one being the effect of CPI on internet penetration (IP) at a 5% significance level (p = 0.0553), highlighting the role of good governance in driving digital transformation. These findings underscore that tax reform is not solely influenced by fiscal policies but also by macroeconomic stability, governance effectiveness, and digitalization. Therefore, the integration of fiscal, regulatory, and technological strategies is crucial in developing a more efficient, equitable, and sustainable tax system. These dynamics have significant implications for tax ratio adjustments in each country, emphasizing the need for evidence-based policies to optimize tax revenue and strengthen economic resilience in the digital era.
Keywords: Tax reform; Tax ratio; corruption perception index; internet penetration; inflation; e-filing; governance quality; Toda-Yamamoto causality